PERANCANGAN SISTEM INFORMASI PENERIMAAN SISWA BARU (PSB) ONLINE PADA MADRASAH TSANAWIYAH (MTs) AL GOTSIYAH JAKARTA - Fajar Akbar; Mochamad Wahyudi; Sumanto (Jurnal Sistem Informasi, 2014)
Abstract -New Student Accepting System on MTs Al Gaotsiyah Jakarta all this time still utilizes manually, So slows process that happens with about problem aught. About problem which emerges is its a lot of prospective registrant which want to do registration and there are many prospective registrant which just wants to ask information therefore causative bustle happening out of focus service, and less research it officers in does penginputan data. psb's information system online offer trouble-shooting that adequately correct reduce aught constraint, psb's information system online it berbasiskan web becomes each information can at access wherever and whenever, so each student candidate that wants to register while wants to do registration can do online ala, so can settle constraint and ketrbatasan whatever available on MTs Al Gaotsiyah Jakarta.